2016
DOI: 10.5014/ajot.2017.023176
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Occupational Therapy Interventions for Adults With Rheumatoid Arthritis: A Systematic Review

Abstract: The evidence supports interventions within the scope of occupational therapy practice for rheumatoid arthritis, but few interventions were occupation based.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 54 publications
1
45
0
10
Order By: Relevance
“…This improvement can be found with nonpharmacologic interventions, such as cognitive‐behavioral therapy and relaxation or biofeedback interventions that address pain, functional disability, fatigue, sleep, depressive symptoms, anxiety, coping, self‐efficacy, and even tender joints. Other nonpharmacologic interventions that have been shown to be effective are physical activity , occupational therapy , and patient education . These studies highlight the importance of a team approach to disease management as well as the importance of incorporating the patient's perspective in the overall treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…This improvement can be found with nonpharmacologic interventions, such as cognitive‐behavioral therapy and relaxation or biofeedback interventions that address pain, functional disability, fatigue, sleep, depressive symptoms, anxiety, coping, self‐efficacy, and even tender joints. Other nonpharmacologic interventions that have been shown to be effective are physical activity , occupational therapy , and patient education . These studies highlight the importance of a team approach to disease management as well as the importance of incorporating the patient's perspective in the overall treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge about the use of assistive devices among people with advanced cancer is, however, limited. Most research recommending the use of assistive devices tends to focus on people with other chronic conditions (Abdulla et al, 2013;Arbesman & Sheard, 2014;Siegel, Tencza, Apodaca, & Poole, 2017). A systematic review on occupational therapy for community-dwelling elderly people (Steultjens et al, 2004) presents strong evidence of the efficacy of giving advice on relevant assistive devices.…”
mentioning
confidence: 99%
“…This scoping study did not evaluate the effectiveness of Joint protection programs but identified 18 RCTs that can be synthesized to investigate their effectiveness. The two most recent systematic reviews (26,27) provided recommendations from 8 RCTs in total leading to the exclusion of 10 additional trials. Therefore, an update of the most recent evidence is highly recommended.…”
Section: Discussionmentioning
confidence: 99%